CENTRAL ASIA IS A REGION OF FIVE STANS Dispute with Kazakh Eurasianists - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2006)
A so-called Eurasian trend of foreign poli-tical thought born in Kazakhstan is gaining increasingly wider support in this country, the main argument of its proponents being “Kazakhstan bordiers on Central Asia, but it is not a Central Asian country. Ours is a Eurasian state strongly influenced by Europe and Western values. Contrary to what certain politicians and journalists assert, we are not another stan. Saudi Arabia is not our historical landmark:We look to Norway, South Korea, and Singapore.”1 This is what these people think about their country’s place and role in the world after 15 years of independent development. They loathe the very name of their country, which ends in stan. The Eurasian trend of “anti-stan” rhetoric merits serious attention and profound analysis. It is tempting to ask whether the concept of a Eurasian state can be applied to Kazakhstan. This invites the question of where the borders between Kazakhstan, which is “not a Central Asian coun-try,” and Central Asia proper lie, and another broader one about whether the Central Asian countries can cope without Kazakhstan. The statement quoted above turned geopolitics and ideology upside down; it distorted the reg-ularities of geopolitical transformation and the process of national self-identification. I will discuss self-identification ideology in the next section, but for now I would like to analyze the geopolitical implications of the above quotation. Indeed, if Kazakhstan does not belong to Central Asia, where is its place? To which part of Asia does it belong? None of the sources describe it as part of say, northern Asia. Why should it move away from Central Asia? The answers to these questions might clarify the reasons why the country wants to detach itself from Central Asia, but they will hardly identify the geographical boundary between “Eurasian” Kazakhstan and Central Asia proper. In fact, Kazakhstan’s Eurasian nature is nothing but a myth or, rather, a geopolitical provocation; the same applies to the idea of Eurasianism, which spells rejection of independence and withdrawal into Eurasian nonexistence. Eurasianism is a conception and philosophy designed to formulate the principles of Russia’s statehood; it is a philosophy of uniting lands for Russia and around it, therefore Russia alone is a Eurasian state. Neither Kazakhstan, nor any other CIS republic, belongs to this category. The Eurasian concept can be applied to the post-Soviet states only in the geographical context, it has nothing to do with the self-identification of either countries or nations.